ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM MENUNJANG PENGENDALIAN INTERNAL PEMBIAYAAN KREDIT USAHA MIKRO PADA PT BANK SULUTGO - Sawori, Roslin; Morasa, Jenny; Tangkuman, Steven J. (Universitas Sam Ratulangi, 2018)
The credit provided by PT SulutGo Bank is very helpful to the community in obtaining its business capital. The problems that often arise in credit are bad debts, and this risks the smooth operation of the bank. This research aims to determine the application of accounting information systems in supporting the internal control of micro business credit financing at PT SulutGo Bank to get a clear picture of this application. This research uses descriptive analysis method. The type of data used in this research is qualitative data. The result showed that the application of the micro finance credit information systems at PT SulutGo Bank has been carried out well and has supported the internal control of micro business credit financing. This is indicated by elements of the accounting information system that supports each component of internal control. Keywords:Â application of accounting information system, internal control